Segmentation of large brain lesions. - Hojjatoleslami, S.A (IEEE Transactions on medical imaging)
This paper describes a region-growing algorithm for the segmentation of large lesions in T 1-weighted magnetic resonance (MR) images of the head. The algorithm involves a gray level similarity criterion to expand the region and a size criterion to prevent from over-growing outside the lesion. The performance of tile algorithm is evaluated and validated on a series of pathologic three-dimensional MR images of the head.